Denosumab in the treatment of delayed hypercalcemia after rhabdomyolysis - Nabil W.G. Sweis; Ahmed Noor; Karen Jong; Joseph L. Zapater (Journal of Clinical and Translational Endocrinology Case Reports, 2025)
Background/objective: Rhabdomyolysis-associated hypercalcemia has limited management options in oliguric patients. Our objective is to describe a case of refractory rhabdomyolysis-associated hypercalcemia with concomitant anuria that was treated with denosumab. Case presentation: A 57-year-old woman with hypertension, hyperlipidemia, and rheumatic heart disease, presented with four days of fever, chills, and right upper quadrant pain. Home medications included simvastatin and warfarin. Initial workup was notable for pyelonephritis and Escherichia coli bacteremia, and she was admitted for urosepsis. Her course was complicated by acute kidney injury requiring continuous renal replacement therapy and new-onset atrial fibrillation managed with amiodarone. During recovery, she developed rhabdomyolysis and concurrent anuria managed with intermittent hemodialysis. As rhabdomyolysis resolved, she developed hypercalcemia with a corrected calcium of 16.4 mg/dL (range, 8.6–10.6 mg/dL). Labs also showed a parathyroid hormone (PTH) level of 62 pg/mL (range, 12–88 pg/mL), and a phosphorus of 6.0 mg/dL (range, 2.5–4.5 mg/dL). Malignancy workup was unremarkable. She received four doses of calcitonin alongside cinacalcet without improvement. Daily hemodialysis was then performed with transient calcium improvements. Ultimately, she received denosumab 60 mg with normalization of serum calcium within a week. Discussion: Severe hypercalcemia during recovery from rhabdomyolysis is challenging to manage in patients who are oliguric and/or anuric and may require denosumab for urgent normalization of the serum calcium level. Conclusion: Denosumab may be an effective option for rhabdomyolysis-associated hypercalcemia in patients with renal impairment who do not respond to dialysis and may not tolerate bisphosphonates.